(untitled) (Bangladesh Journal of Medical Science, 2010)
Objective: To study the clinical, radiological and histopathological characteristics along with the management outcome of salivary gland neoplasm. Materials and Methods: This study included thirty two patients (16 male and 16 female) with salivary gland tumours presented at Combined Military Hospital Dhaka, Apollo Hospital Dhaka and Ibn Sina Medical College and Hospital Dhaka from January 2006 to December 2009. The data of each patient included age, sex, presenting symptoms and signs, provisional diagnosis, preoperative investigations, operation notes, histopathological examination and state at follow up. Results: The mean age was 42.5 years. 14 (43.75%) patients presented at 5th decade. Main presenting symptom was swelling (100%) followed by pain (18.75%). All patients underwent fine needle aspiration cytology which was conclusive in 26 patients (81.25%). Thirty one patients underwent surgical excision. 24 cases were parotid neoplasm and 8 cases were submandibular neoplasm. 20 patients (16 parotid and 4 submandibular) were pleomorphic adenoma. Conclusion: There is no substitute for detailed clinical history and examination in the assessment of salivary gland neoplasm. Imaging studies are probably academic but determine the extent of the disease. Early diagnosis, adequate and proper treatment improves the prognosis. Key words: Salivary gland tumour; Pleomorphic adenoma; Warthin’s tumour; Adenoid cystic carcinoma; Mucoepidermoid carcinoma. DOI: 10.3329/bjms.v9i2.5656 Bangladesh Journal of Medical Science Vol.09 No.2 Apr 2010 pp.87-94